2015
DOI: 10.1007/978-3-319-22701-6_5
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Concurrent and Retrospective Verbal Protocols for Blind and Sighted Users

Abstract: Abstract. Verbal protocols are widely used in user studies for evaluating websites. This study investigated the effectiveness and efficiency of concurrent and retrospective verbal protocols (CVP and RVP) for both blind and sighted participants, as well as participant workload and attitudes towards these methods. Eight blind and eight sighted participants undertook both protocols in a website evaluation. RVP was more effective as measured by problems encountered for both groups, although it was no more efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…6 Furthermore, Hoc and Leplat (1983) demonstrated that the retrospective verbal protocol, if accompanied by aided recall , is better suited than the concurrent verbal protocol to measure the cognitive processes implemented during a problem-solving task. 7 Finally, Savva et al (2015) found that because of its greater effectiveness, the retrospective verbal protocol “is a more useful protocol for practitioners and researchers even though it takes more time and is more demanding for participants” (p. 55).…”
Section: Methods For Studying the Real-time Creative Processmentioning
confidence: 99%
“…6 Furthermore, Hoc and Leplat (1983) demonstrated that the retrospective verbal protocol, if accompanied by aided recall , is better suited than the concurrent verbal protocol to measure the cognitive processes implemented during a problem-solving task. 7 Finally, Savva et al (2015) found that because of its greater effectiveness, the retrospective verbal protocol “is a more useful protocol for practitioners and researchers even though it takes more time and is more demanding for participants” (p. 55).…”
Section: Methods For Studying the Real-time Creative Processmentioning
confidence: 99%
“…Numerous studies have compared the two protocols in terms of the participants' task success or the number of problems revealed [2], [15,16,17,18,19]. However, there is little research into the differences in the types of problems that the two protocols reveal [16,17,18,19] and these studies have been conducted only with sighted participants.…”
Section: Introductionmentioning
confidence: 99%